The effect of using action research in developing twenty-first century skills for geography teachers at the secondary stage in Al Mahwit city - Al-Adwani, Khaled Mutahar Hussein; Al-Salahi, AbdulSalam Muhammad Ahmad; Al-Faqih, Najat Hassan Hassan (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the impact of the use of procedural research in developing the skills of the twenty-first century for geography teachers in the secondary stage in the city of Al-Mahwit in the Republic of Yemen. (65) performance indicators distributed over three main areas, and the experiment was applied to a sample of (24) male and female secondary school teachers in Al Mahwit city schools. The tool as a whole and in each of the main areas and for each of the skills in favor of the post application, The size of the total effect was (0.97), it means a large degree, and based on the results, the researchers made a number of recommendations, the most important of which is the adoption of procedural research as an entry point for sustainable professional development within the school, and support for geography teachers at the secondary level and encouraging them to implement procedural research in addition to future proposals in the subject.
Keywords: Action research; 21st century skills; geography teachers; High school